2014
DOI: 10.1007/s00776-013-0487-x
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle versus free frozen autograft for reconstruction in malignant bone and soft tissue tumors of the lower extremities

Abstract: Background Of the biological reconstruction methods for malignant bone and soft tissue tumors, reconstruction with liquid nitrogen has the advantage of maintaining continuity on the distal side of the tumor bone site (pedicle freezing procedure; PFP). This method is expected to result in early blood flow recovery, with early union and low complication rate. The purpose of this study was to compare the outcomes of the PFP and free freezing procedure (FFP) in the lower extremities. Methods The study included 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…The average bone union time for the 29 patients who did not require additional surgery was ten months (range, 3-36) and the time was not significantly different between the FFP (10.2 months) and the PFP (9.8 months). In a previous study performed by Shimozaki et al, bone union was reportedly 9.8 months using FFP and 4.8 months using the PFP [25]. In our study, the nonsignificant difference between procedures could be explained by the older mean age of patients treated with the PFP (45 years) than with the FFP (24 years); moreover, the FFP also included the hemicortical resection group which had a shorter mean bone union time (6.5 months).…”
Section: Discussionmentioning
confidence: 88%
“…The average bone union time for the 29 patients who did not require additional surgery was ten months (range, 3-36) and the time was not significantly different between the FFP (10.2 months) and the PFP (9.8 months). In a previous study performed by Shimozaki et al, bone union was reportedly 9.8 months using FFP and 4.8 months using the PFP [25]. In our study, the nonsignificant difference between procedures could be explained by the older mean age of patients treated with the PFP (45 years) than with the FFP (24 years); moreover, the FFP also included the hemicortical resection group which had a shorter mean bone union time (6.5 months).…”
Section: Discussionmentioning
confidence: 88%
“…Shimozaki et al 38 reported better union times and lower postoperative complications for the pedicle-freezing technique, which they thought was caused by an early blood flow recovery. Benedetti et al 29 compared the functionality of allograft-prosthesis composites with that of tumor prosthesis reconstruction and found a better hip abductor and hip flexor motor power in the allograft prosthesis-composite group; in gait a Autoclaving: Heated at 120°C for 10 min.…”
Section: Discussionmentioning
confidence: 99%
“…It may be the case that, as mentioned above, frozen bone preserves bone morphogenetic protein and its osteoinductive ability better than hyperthermic treatments such as autoclaving and pasteurization [22]. Furthermore, if the pedicle-freezing procedure method, which is a specific procedure of frozen autografts and distinguishes from other recycled bone, is possible, the number of osteotomy sites can be decreased, allowing for a faster bone union [25]. In addition, these biological reconstruction techniques have issues, such as requiring extracorporeal devices, which make it more likely that the resected bone will be contaminated, whereas the frozen autograft method uses simple surgical techniques without complicated temperature control and special devices.…”
Section: Discussionmentioning
confidence: 99%